2004
DOI: 10.1089/jmf.2004.7.472
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Effect ofBoerhavia diffusa: Effect on Serum and Tissue Lipids in Experimental Diabetes

Abstract: The present study was designed to investigate the antihyperlipidemic activity of an aqueous extract of Boerhavia diffusa leaves in alloxan diabetic rats. Hyperlipidemia is an associated complication of diabetes mellitus. Many herbs and spices are known to be antihyperglycemic. Oral administration of B. diffusa leaf extract (BLEt) at 200 mg/kg of body weight for 4 weeks resulted in significant reduction in serum and tissue cholesterol, free fatty acids, phospholipids, and triglycerides. Moreover, BLEt supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…Partial restoration of the pancreatic islet cells after treatment with the extract indicate that the possible mechanism by which the methanolic extract of F. aestuans reduced blood glucose levels of the diabetic rats may be either by increasing the pancreatic secretion of insulin from the islet of Langerhan's or it is released from bound insulin. Similar result has been reported (Pari et al, 2004). Recently, Mgbeje et al (2016) found that there was a significant reduction in the blood glucose levels of rats treated with n-hexane fraction of Heinsia crinite whencompared with the diabetic control (Mgbeje et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Partial restoration of the pancreatic islet cells after treatment with the extract indicate that the possible mechanism by which the methanolic extract of F. aestuans reduced blood glucose levels of the diabetic rats may be either by increasing the pancreatic secretion of insulin from the islet of Langerhan's or it is released from bound insulin. Similar result has been reported (Pari et al, 2004). Recently, Mgbeje et al (2016) found that there was a significant reduction in the blood glucose levels of rats treated with n-hexane fraction of Heinsia crinite whencompared with the diabetic control (Mgbeje et al, 2016).…”
Section: Discussionsupporting
confidence: 76%
“…Phospholipids are vital part of biomembrane rich in PUFA, which are susceptible substrate for free radicals such as O 2 •- and OH • radicals [42]. Increased phospholipids levels in tissues were reported by [43,44] in streptozotocin diabetic rats. Administration of Diasulin decreased the levels of tissue free fatty acids and phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipids are present in cell membrane and make up the vast majority of the surface lipoprotein forming a lipid bilayer that acts as an interface with both polar plasma environment and non-polar lipoprotein of lipoprotein core [58]. Increased phospholipids level in tissues was reported by Venkateswaran et al [59] and Pari and Satheesh [60] in streptozotocin-induced diabetic rats. Administration with the stem and leaf ethanol extracts of B. nervosa and glibenclamide decreased the level of phospholipids.…”
Section: Discussionmentioning
confidence: 99%